Dude bro party massacre III [videorecording (DVD)] - Oswalt, Patton, 1969-; Sestero, Greg, 1978-; Owen, Alec (Scream Team Releasing, 2019)
In the wake of two back to back mass murders on Chico's frat row, loner Brent Chirino must infiltrate the ranks of a popular fraternity to investigate his twin brother's murder at the hands of the serial killer known as Motherface.